PTU-196 Small Bowel Capsule Endoscopy – a Retrospective Analysis of 348 Cases from Qeii and Lister Hospitals. (4th June 2013) - Evans, J A; Beg, S; Nathwani, R; Samsheer, K; Ebro, E; Turnbull, E
Abstract : Introduction: Small bowel capsule endoscopy (SBCE) is a useful diagnostic tool for investigating iron deficiency anaemia (IDA) and suspected Crohn's disease (CD) 1, 2, but its use is often limited to specialist teaching centres. We aim to establish whether SBCE is a useful tool when employed in a district general hospital (DGH) setting. Methods: We retrospectively analysed the data of all SBCE carried out at QEII and Lister hospitals over 36 months since its introduction in 2009 using the GIVEN Pillcam SB 2 system. Patient demographics, indications, previous investigations, SBCE findings and how these altered management were reviewed. Results: 348 studies were performed on 175 males and 173 females; the mean age was 54.3 years (range 17–86). 207/348 (59%) revealed some form of pathology. 7 studies were incomplete (2.01%). Patency capsules were used in those with suspected risk of stricturing pathology for 22/348 cases (6.32%). No cases required surgical retrieval of a capsule. The most common indication for SBCE was IDA = 185/348 studies (53.1%). The next most common indication was suspected CD = 141/348 (40.5%). All patients had undergone bi-directional endoscopy prior to SBCE. The commonest findings were; small bowel (SB) erosions/ulcers (65 cases) SB angiodysplasia (39 cases) CD (21 cases) SB ulcers (19) polypoidal masses (13 cases) and fresh blood (11 cases). 3 cases of lymphoma and one of Enterobius vermicularis were discovered. Where IDA was the indication, 65/185 studies (35.1%) had findings that led to an alteration in management. In studies for suspected CD, 44/141 (31.2%) had findings that led to an alteration in management. Conclusion: For IDA the diagnostic yield of 35% is in keeping with previously published data, which shows that SBCE can identify a source of bleeding in 31- 76%1. For CD we identified abnormal pathology requiring further intervention in 31% of cases. It is debatable whether a small number of terminal ileal ulcers is sufficient to diagnose CD. If greater than 3 are seen, histological confirmation of CD is attempted via repeat endoscopy. 9 of the 348 patients had previously undergone a SBCE and the less invasive nature of SBCE lends itself to repeated use for small bowel CD surveillance. SBCE is a reliable, safe and useful tool in the setting of a DGH setting for identifying small bowel pathology and should not be restricted to specialist centres. Disclosure of Interest: None Declared. References: R Sidhu, D Sanders, A Morris, M McAlindon. Guidelines on small bowel enteroscopy and capsule endoscopy in adults. BSG Guidelines. Gut 2008; 57:125–136. SK Patel, P Mairs. A Review of Small Bowel Capsule Endoscopy Performed At Darent Valley Hospital Since Its Introduction in 2006. The Online Journal of Clinical Audits. 2011; Vol 3(3)